The Implementation of Cooperative Learning Model Type STAD in Badminton Learning for Elementary School Students - Yayang Mochamad Dewantara; Ani Kurniawati; Zaenal Arifin (Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to obtain information for improving the activity and learning outcomes of basic long serve and short serve techniques in badminton learning through cooperative learning model type STAD in Grade VI, Muarasanding I Elementary School. This research used classroom action research method. The data were obtained from the results of badminton long serve and short serve tests. The test results in the first cycle showed that 7 students (35%) had not achieved the long serve, while 4 students (20%) had not completed the short serve. To maximize learning to achieve the completeness, the researcher used the second cycle program in this research.